Structural basis for recognition of the nonclassical MHC molecule HLA-G by the leukocyte Ig-like receptor B2 (LILRB2/LIR2/ILT4/CD85d) - Shiroishi, Mitsunori (National Academy of Sciences, 2006)
HLA-G is a nonclassical MHC class I (MHCI) molecule that can suppress a wide range of immune responses in the maternal–fetal interface. The human inhibitory immune receptors leukocyte Ig-like receptor (LILR) B1 [also called LIR1, Ig-like transcript 2 (ILT2), or CD85j] and LILRB2 (LIR2/ILT4/CD85d) preferentially recognize HLA-G. HLA-G inherently exhibits various forms, including β(2)-microglobulin (β(2)m)-free and disulfide-linked dimer forms. Notably, LILRB1 cannot recognize the β(2)m-free form of HLA-G or HLA-B27, but LILRB2 can recognize the β(2)m-free form of HLA-B27. To date, the structural basis for HLA-G/LILR recognition remains to be examined. Here, we report the 2.5-Å resolution crystal structure of the LILRB2/HLA-G complex. LILRB2 exhibits an overlapping but distinct MHCI recognition mode compared with LILRB1 and dominantly recognizes the hydrophobic site of the HLA-G α3 domain. NMR binding studies also confirmed these LILR recognition differences on both conformed (heavy chain/peptide/β(2)m) and free forms of β(2)m. Binding studies using β(2)m-free MHCIs revealed differential β(2)m-dependent LILR-binding specificities. These results suggest that subtle structural differences between LILRB family members cause the distinct binding specificities to various forms of HLA-G and other MHCIs, which may in turn regulate immune suppression.